2014
DOI: 10.1016/j.jalz.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The Israel Diabetes and Cognitive Decline (IDCD) study: Design and baseline characteristics

Abstract: Background Type 2 diabetes (T2D) is associated with increased risk of dementia. The prospective longitudinal Israel Diabetes and Cognitive Decline study aims at identifying T2D-related characteristics associated with cognitive decline. Methods Subjects are population-based T2D 65+, initially cognitively intact. Medical conditions, blood examinations, and medication use data are since 1998; cognitive, functional, demographic, psychiatric, DNA, and inflammatory marker study assessments were conducted every 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 45 publications
3
66
0
Order By: Relevance
“…Detailed methods of the IDCD are reported in the Supplementary Materials and in Beeri et al [4]. Participants in the IDCD study were randomly selected from T2D individuals in the MHS Diabetes Registry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed methods of the IDCD are reported in the Supplementary Materials and in Beeri et al [4]. Participants in the IDCD study were randomly selected from T2D individuals in the MHS Diabetes Registry.…”
Section: Methodsmentioning
confidence: 99%
“…Participants completed a broad neuropsychological battery [4], the basis for the outcome measures. Factor analysis summarized the neuropsychological measures into four domains: language/semantic categorization (similarities, letter fluency, category fluency), episodic memory (immediate recall, delayed recall, and recognition), executive functioning (trails A and trails B, constructional praxis, and digit symbol), and attention/working memory (diamond cancellation, digit span forward, and digit span backward).…”
Section: Methodsmentioning
confidence: 99%
“…Participants in the IDCD study were randomly selected from the approximately 11,000 T2D individuals in the MHS Diabetes Registry, maintained since 1998 [22]. The design and rationale of the IDCD has been described in detail elsewhere [2224]. Briefly, participants included in the study had confirmed T2D, were initially cognitively normal (based on a Clinical Dementia Rating scale [25] score of zero and a multidisciplinary consensus conference), were above the age of 65, lived in central Israel, were fluent in Hebrew, had at least one informant, did not have any neurological or psychiatric conditions potentially affecting cognition (e.g., schizophrenia, stroke), and had at least two HbA1c assessments.…”
Section: Methodsmentioning
confidence: 99%
“…The Israel Diabetes and Cognitive Decline [(IDCD) (Beeri et al, 2014)] sample consists of elderly Israeli Jewish (≥65 years old) T2D subjects, cognitively normal at entry to the study, taking part in a longitudinal investigation for evaluation of the relationship of cognitive decline and long-term T2D characteristics. Participants, residing in Isreal’s central region, were randomly selected from the diabetes registry of the Maccabi Healthcare Services (MHS).…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were categorized by having ever/never taken the medication (Table 1). For further information regarding the IDCD sample, see Beeri et al (2014).…”
Section: Methodsmentioning
confidence: 99%